Prophylactic internal iliac artery balloon for caesarean in placenta accreta reduces haemoglobin drop – Retrospective comparative study - Yuen Yee Yannie Chan; Ellen Lok-Man Yu; Tsz Kin Lo (Journal of Obstetrics and Gynaecology)
Background This study compared maternal and foetal outcomes of managing placenta accreta spectrum (PAS) disease with and without prophylactic internal iliac balloon occlusion (IIABO) at a tertiary hospital between 2002 and 2021.Methods This retrospective cohort study included patients with confirmed PAS disorder, comparing maternal and foetal outcomes between those who underwent IIABO before caesarean delivery and those who did not, both receiving standardised multidisciplinary care. Primary outcomes included perioperative haemoglobin drop. Secondary outcomes included estimated blood loss, transfusion rate, operative duration, ICU stay, hysterectomy rates, and newborns’ Apgar scores.Results Thirty-one antenatally diagnosed PAS patients were analysed (IIABO n = 21, non-IIABO n = 10). Over 90% had prior caesarean deliveries. IIABO is associated with lower intraoperative haemoglobin drop (p < .001) and higher postoperative haemoglobin (p = 0.047). The linear regression model demonstrated that IIABO and classical caesarean significantly reduced intraoperative blood loss (p = 0.019). No differences were seen in operative time, ICU stay, hysterectomy rates, or newborn Apgar scores. No IIABO-related complications were reported.Conclusion Prophylactic IIABO during caesarean delivery for PAS is associated with less haemoglobin drop and higher postoperative haemoglobin. IIABO under local anaesthesia was feasible, possibly reducing risks tied to extended general anaesthesia. Larger studies are recommended to support the role of IIABO in PAS disorders.